Relationship between school refusal behavior and social functioning: a cluster analysis approach (European Journal of Education and Psychology, 2019)
On the basis of the heterogeneous casuistry that characterizes the students who refuse going to school, it is useful to have a classification of this population in homogeneous groups. For this, the aim of this study was, first, to identify by cluster analysis the profiles of school refusal behavior based on the functional model evaluated through the School Refusal Assessment Scale-Revised (SRAS-S). Secondly, it is intended to analyze if there are differences in social functioning scores according to the school refusal profiles identified. This study involved 1212 Spanish children between 8 and 11 years old (M=9.12, SD=1.05) who completed the SRAS-R to evaluate the school refusal behavior and the Child and Adolescent Social Adaptive Functioning Scale (CASAFS) to assess social functioning. Four profiles were identified: Non-school refusers, School refusers by mixed reinforcements, School refusers by tangible reinforcements and School refusers by negative reinforcements. The profile of Non-school refusers achieved the highest average scores in social functioning, while School refusers by mixed reinforcements group obtained the lowest average scores in social functioning. In general, the profiles found support the clusters identified in previous studies. The implications of social functioning on school refusal behavior are discussed.